Narasi Akuntan di Balik Angka: Studi Etnografi tentang Pengambilan Keputusan Etis (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to understand how professional accountants navigate ethical dilemmas in decision-making across various sectors, including public, private, and governmental institutions. The main issues addressed are organizational pressure, conflicts with personal values, and organizational culture in ethical decision-making. A qualitative approach using ethnographic methods was employed, collecting primary data through interviews with 20 professional accountants, as well as secondary data from organizational documents such as professional codes of ethics and internal policies. Data analysis was conducted through reduction, presentation, and conclusion drawing, with validation using triangulation techniques. The findings indicate that organizational pressure is the dominant factor influencing ethical decision-making, particularly in the private sector, where 70% of respondents reported experiencing such pressure. Despite this, 85% of respondents stated that they upheld personal values such as integrity, although 15% admitted compromising those values due to external pressures. Ethical organizational culture was found to be stronger in government and educational sectors compared to the private sector. The main strategies used by accountants to address ethical dilemmas were consulting with colleagues (55%) and referring to professional codes of ethics (30%). The study concludes that organizational pressure, personal values, and organizational culture play significant roles in shaping ethical decisions among accountants. Therefore, it is essential for organizations to strengthen ethical culture, provide professional training, and establish support mechanisms that protect accountants in the face of external pressures.